Finite Element Analysis of R.C Beams Using Steel Scraps Under Cyclic Loading Using ETABS - Subramani, T; Nashreen, R (International Journal of Engineering and Technology, 2018)
In the modern trend peoples are looking for alternate material which is cost effective and high stability in while subject to dynamic loading. Considering this as one of the factor in our proposed we choose steel scrap as reinforced material which has high durability and strength. To find out the withstanding capacity ofÂ  the dynamic loading model the structure using finite element software and analysis to predict the safety of the structure. From the analysis result we conclude for preventive measure of the structural failure and utilization of extra dampers has find out. To validating the result, analytical work is carried out and implemented by using ETAB software. Â Â